Impact of Climate Change on Public Health in Rwanda - Fidele, Nizeyimana; Jean Marie Vianney, Nkurikiyintwali; Simeon, Tuyishime; Jeanne d’Arc, Mukeshimana; Felix, Niyonkuru; Pasteur, Butoya; Mupenzi Jackline, Gatsinzi; Potien, Uwihoreye (Journal of Weather Changes, 2024)
Rwanda is a small Central African country. A land with thousands of hills and mountains. It is a low-income country and one of Africa's fastest-growing economies. It is home to a variety of ecosystems, such as mountainous rainforests, gallery forests, savanna woodlands, wetlands, aquatic forests, and agroecosystems. From rising temperatures to changing rainfall patterns, the hidden dangers of climate change are unmasking themselves in the form of various health risks. Every year, many deaths, bodily injuries, and house collapses, among other repercussions, are documented as detrimental effects of climate change events on public health. This article delves into the intricate relationship between climate change and public health in Rwanda, exploring the adverse effects it has on vulnerable communities. By shedding light on this pressing issue, we can better understand the urgency of taking action to mitigate the impact of climate change on public health as well as potential solutions to the current predicament. The authors researched several literatures to develop their perspectives on the subject and explored potential solutions to protect the well-being of Rwandans in the face of this global crisis.
Keywords: Rwanda; climate change; public health; temperatures; rainforest